Pismeni zadaci

Zadatak 0229

Test: MKsIIJAII_047

 

Reši jednačinu:

 \(\frac{2x-5}{x-11}+\frac{7-3x}{(x-6)^2+1}=\frac{x-4}{x-11}+\frac{(x-3)^2}{(x-6)^2+1}\).

 

Rešenje:


 

\(\frac{7-3x}{(x-6)^2+1}-\frac{(x-3)^2}{(x-6)^2+1}=\frac{x-4}{x-11}-\frac{2x-5}{x-11}\)

\(\frac{7-3x-x^2+6x-9}{(x-6)^2+1}=\frac{x-4-2x+5}{x-11}\)

\(\frac{+3x-x^2-2}{x^2-12x+37}=\frac{-x+1}{x-11}\)

\((3x-x^2-2)(x-11)=(-x+1)(x^2-12x+37)\)

\(3x^2-x^3-2x-33x+11x^2+22=-x^3+12x^2-37x+x^2-12x+37\)

\(x^2+14x-15=0\)

\(x_{1,2}=\frac{-14\pm \sqrt{196+60}}{2}\)

\(x_{1,2}=\frac{-14\pm 16}{2}\)

\(x_{1}=1,x_{2}=-15\).

 


 

Vi ste ovde: Home Zbirke zadataka Srednja Za II razred Kvadratna jednačina Rešavanje kvadratne jednačine Zadatak 0229